2010
DOI: 10.1021/cm901703d
|View full text |Cite
|
Sign up to set email alerts
|

⟨0001⟩-Preferential Growth of CdSe Nanowires on Conducting Glass: Template-Free Electrodeposition and Application in Photovoltaics

Abstract: By contrast with the rich, wurztite-related, one-dimensional nanostructure of ZnO and its wide variety of applications, there only exists a few methods for the controlled and designed synthesis of one-dimensional CdSe nanostructures. Here, we describe a low-temperature and directed preparation of CdSe nanowires in a simple one-step, template-free electrochemical deposition. The preparation takes advantage of both the wurtzite structure characteristics and current-induced preferential orientation. High-resoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 31 publications
0
43
0
1
Order By: Relevance
“…Bulk heterojunction PV devices utilizing zinc oxide nanowire arrays have shown high performance when prepared in conjunction with a variety of active materials including P3HT [3,4], PCBM:P3HT [5,6], CdS [7,8], dye-sensitizers [9,10] and colloidal quantum dot (QD) thin films [1]. The minority carrier diffusion length in the active material of these devices lies in the nano-to micrometer length scale.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk heterojunction PV devices utilizing zinc oxide nanowire arrays have shown high performance when prepared in conjunction with a variety of active materials including P3HT [3,4], PCBM:P3HT [5,6], CdS [7,8], dye-sensitizers [9,10] and colloidal quantum dot (QD) thin films [1]. The minority carrier diffusion length in the active material of these devices lies in the nano-to micrometer length scale.…”
Section: Introductionmentioning
confidence: 99%
“…Many II-IV group nanorods, such as CdS, CdSe, CdTe, ZnS, ZnSe, and ZnTe, have been successfully synthesized in colloidal solutions [17][18][19][20][21][22]. However, except ZnO [23], there are only a few reports that describe the fabrication of aligned II-IV nanorod or nanowire arrays without involving of catalyst and/or templates [24][25][26][27][28]. Xiong et al have succeeded in growing the CdS, CdSe, and CdTe nanorod arrays on meca using CVD method [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al and Jiang et al have independently reported the synthesis of ordered arrays of wurtzite CdS nanowires on Cd-foil substrates via solvothermal route [26,27]. Zhou et al have fabricated CdSe nanowire arrays on ITO (tin-doped indium oxide) by electrochemical approach [28]. Most recently, Chen' group has developed a non-template hydrothermal method to grow CdS nanorod arrays (CdS NRs) on ITO substrate by using glutathione as capping agents [29].…”
Section: Introductionmentioning
confidence: 99%
“…These features make them desirable for use in various applications. As illustrations, II-VI NWs have been used in photodetectors [1][2][3][4], solar cells [5][6][7][8][9] and in photocatalytic applications [10,11]. Likewise, IV-VI NWs, especially the lead chalcogenides, have been used in infrared photodetectors [12], thermoelectric devices [13,14] and in field effect transistors (FETs) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%